2013
DOI: 10.1007/s00402-013-1849-8
|View full text |Cite
|
Sign up to set email alerts
|

Periarticular infiltration for pain relief after total hip arthroplasty: a comparison with epidural and PCA analgesia

Abstract: In our study periarticular infiltration was clearly superior to PCA with morphine after THA, providing better pain relief and lower opioid consumption postoperatively. Infiltration seems to be equally effective to epidural analgesia without having the potential side effects of the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
1
25
0
2
Order By: Relevance
“…Prior to submission, we updated searches in December 2013 and identified 12 new studies, three in patients with THR and nine in patients with TKR. Our results for local anaesthetic infiltration in patients receiving THR were supported with reduced pain compared with untreated control [69-71], or similar pain compared with epidural analgesia [71]. The results of our meta-analyses in patients receiving TKR were also supported with improved early pain control in patients receiving local anaesthetic infiltration [72]; further pain reduction with added ketoralac [73,74] but not steroid [75]; and uncertainty when compared with femoral nerve block [76-80].…”
Section: Discussionsupporting
confidence: 59%
“…Prior to submission, we updated searches in December 2013 and identified 12 new studies, three in patients with THR and nine in patients with TKR. Our results for local anaesthetic infiltration in patients receiving THR were supported with reduced pain compared with untreated control [69-71], or similar pain compared with epidural analgesia [71]. The results of our meta-analyses in patients receiving TKR were also supported with improved early pain control in patients receiving local anaesthetic infiltration [72]; further pain reduction with added ketoralac [73,74] but not steroid [75]; and uncertainty when compared with femoral nerve block [76-80].…”
Section: Discussionsupporting
confidence: 59%
“…3). In addition to the RCTs included in the two pairwise meta-analyses, Bayesian network meta-analysis included 10 more RCTs [3,12,14,19,32,45,48,53,55,61] comparing use of local infiltration analgesia or peripheral nerve blocks with epidural analgesia or intrathecal morphine. By introducing the additional indirect comparisons (epidural analgesia, intrathecal morphine) we increased the power and precision of the network meta-analysis (Appendix 1.…”
Section: Discussionmentioning
confidence: 99%
“…We combined intervention arms in three studies: single-shot and continuous local infiltration analgesia [54]; continuous lumbar plexus block and continuous femoral nerve block [39]; and femoral nerve block and pudendal and paracervical block [7]. For the pairwise metaanalysis, the epidural analgesia arm was excluded for two studies [45,53]. The combination of intervention arms and exclusion of the epidural analgesia arm was performed according to the Cochrane Collaboration guidelines [25].…”
Section: Data Synthesismentioning
confidence: 99%
“…After reading full texts, 7 citations which did not fulfill the inclusion criteria were excluded. Finally, 9 RCTs were identified in our study ( Figure 1) [10][11][12][13][14][15][16][17][18].…”
Section: Search Resultsmentioning
confidence: 98%
“…Studies have shown that LIA is consistently more effective in the treatment of postoperative pain after TKA or THA when compared with placebo [8,9]. Comparison between LIA and epidural analgesia was conducted by several authors, which was more convincing to illustrate its superiority [10][11][12][13][14][15][16][17][18]. Tsukada et al [16] have shown that local infiltration was associated with a lower visual analog scale (VAS) score and better flexion motion than epidural analgesia, while Jules-Elysee et al [14] reported that epidural analgesia provided less opioid and a lower VAS score.…”
Section: Introductionmentioning
confidence: 99%